Means of Training Perception for Primary School Children: the Essence and the Systematization - Barbashova, I. (Pedagogical Discourse, 2016)
The article states that means of training perception for primary school children is a variety of objects (natural and artificial), instruments, devices and equipment that are used as carriers of information about the external properties of objects and phenomena surrounding, subjective instruments of cooperation in training and perceptual activity. The necessity of usage of certain means, their complexes and systems has been proved. The author states that means of training perception for primary school children is a subsystem of educational environment; it is designed to create the necessary conditions for effective and safe achievements of goals of sensory development of primary school children. At the same time it is a subsystem of global educational space – a part of unlimited subject area of the objective world, which is associated with large-scale phenomena in education. The author has defined the main functions of means of training perception. They are: compensatory, adaptive, informative, integrative, instrumental. The author has justified the four groups of systematization of training means according to the character of reality reflection. The first group includes natural objects (real objects, collections, instruments and accessories, materials, tools); the second one includes image and reflection of properties of external reality objects (subject pictures, planar and three-dimensional models, models, models, videos, audio);the third group contains descriptions of properties of external reality objects, conventional signs and symbols (tables, process maps, cards for individual work, graphic marks); the fourth group is represented by hardware (teacher’s personal computer, student’s personal computer, educational software, multimedia, interactive boards, classroom blackboards and chalk, patterned cloth, TV, tape recorder, VCR, teacher’s synthesizer, pupil’s synthesizer). According to this typology, the author has characterized teaching means of color and spatial visual perception, phonetic and musical perception, physical, mechanical and tactile spatial perception. The particular attention is paid to the analysis of sensory-developing resource of pedagogical means, which is included in curricula of Ukrainian language, Mathematics, Arts and Music, Labor Training.